2006
DOI: 10.1021/bp060067b
|View full text |Cite
|
Sign up to set email alerts
|

Localization Effect on the Metal Biosorption Capability of Recombinant Mammalian and Fish Metallothioneins in Escherichia coli

Abstract: In this study, we examined the expression of mammalian and fish metallothioneins (MTs) in Escherichia coli as a strategy to enhance metal biosorption efficiency of bacterial biosorbents for lead (Pb), copper (Cu), cadmium (Cd), and zinc (Zn). In addition, MT proteins were expressed in either the cytoplasmic or periplasmic compartment of host cells to explore the localization effect on metal biosorption. The results showed that MT expression led to a significant increase (5-210%) in overall biosorption efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Besides, it needs no trans-membrane transportation of the heavy metals. Expression of MT in E.coli as fusions to membrane proteins was reported on Cd bioaccumulation [29,30]. A more than 5 fold increase of Cd binding capacity was obtained [31].…”
Section: Bioaccumulation Of As(iii) In Bkåçäá=(pghm) Under Various Comentioning
confidence: 98%
“…Besides, it needs no trans-membrane transportation of the heavy metals. Expression of MT in E.coli as fusions to membrane proteins was reported on Cd bioaccumulation [29,30]. A more than 5 fold increase of Cd binding capacity was obtained [31].…”
Section: Bioaccumulation Of As(iii) In Bkåçäá=(pghm) Under Various Comentioning
confidence: 98%
“…A reported method was used to analyze the bioaccumulation capacity of E. coli expressing SaMT3 [16]. After induction with 500 μM IPTG for 12 h, E. coli were centrifuged at 5,000 g for 10 min.…”
Section: Bioaccumulation Capacity Of E Colimentioning
confidence: 99%
“…Similarly, exogenous expression KcMT2a from Kandelia candel also improved the metal tolerance ability of E. coli cells and metal-binding activities [33]. In order to better compare the bioaccumulation capacity of His and His fused SaMT3 protein, reported concentrations (250 μM, 500 μM, and 1,000 μM) and different time points were used (24 h, 48 h) [16]. These concentrations were frequently used in analyzing the metal-binding capacities of MTs [20].…”
Section: +mentioning
confidence: 99%
“…3 g dry weight/L) for the biosorption experiments. All the glassware used in the biosorption operations was treated with concentrated HNO 3 solution prior to each experiment to avoid possible adsorption of heavy metals on the surface of glass containers [2,4,32].…”
Section: Preparation Of the Bacterial Biosorbentsmentioning
confidence: 99%
“…Recent work showed that expressing mer operon genes encoding for cysteine-containing mercuric ion transport proteins (such as periplasmic protein MerP or inner membrane protein MerT) [2,30,31] on Escherichia coli hosts could make them very effective biosorbents for heavy metals removal. In addition, several other metal-binding proteins, such as metallothioneins (MTs) [32,33], phytochelatins (PCs) [34], and metal-binding peptides [2] were also expressed on E. coli to create powerful biosorbents. Although MerP protein is a target for the development of genetically engineered biosorbents [35], there is little information on utilizing MerP-expressing biosorbents to remove heavy metals (especially for metals other than mercury) [2].…”
Section: Introductionmentioning
confidence: 99%